2011
DOI: 10.1177/0956797611400914
|View full text |Cite
|
Sign up to set email alerts
|

Changes in EEG Cross-Frequency Coupling During Cognitive Behavioral Therapy for Social Anxiety Disorder

Abstract: Coupling between EEG delta and beta oscillations is enhanced among anxious and healthy individuals during anticipatory anxiety. EEG coupling patterns associated with psychotherapy have not yet been quantified in socially anxious individuals. In this study, we used a double baseline, repeated measures design, in which 25 adults with a principal diagnosis of social anxiety disorder completed 12 weekly sessions of standardized group cognitive behavioral therapy and four EEG assessments: two at pretreatment, one a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(108 citation statements)
references
References 37 publications
8
96
4
Order By: Relevance
“…However, the recent and relatively limited literature on this subject is not conclusive. Participant samples that would be expected to experience increased anxiety have been reported to demonstrate increased delta-beta coupling, for instance offspring of anxiety patients (Miskovic et al, 2011a(Miskovic et al, , 2011b. On the other hand, Velikova et al (2010) reported decreased deltabeta coupling in anxiety disorder patients.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…However, the recent and relatively limited literature on this subject is not conclusive. Participant samples that would be expected to experience increased anxiety have been reported to demonstrate increased delta-beta coupling, for instance offspring of anxiety patients (Miskovic et al, 2011a(Miskovic et al, , 2011b. On the other hand, Velikova et al (2010) reported decreased deltabeta coupling in anxiety disorder patients.…”
Section: Discussionmentioning
confidence: 89%
“…Several papers support a hypothesis that delta-beta coupling may reflect cortical/sub-cortical crosstalk involved in affect regulation (Schutter and van Honk, 2005b;Schutter et al, 2006;van Peer et al, 2008;Velikova et al, 2010;Miskovic et al, 2010Miskovic et al, , 2011aMiskovic et al, , 2011b; for a review, see Schutter and Knyazev, in press). Theoretical models that suggest an important role for attentional control in affect regulation point at mediation of such processes through cortical/sub-cortical reciprocal networks (Ochsner and Gross, 2005;McRae et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Typical EEG-aBCI features involve the calculation of specific EEG frequency subband powers, such as delta, theta, alpha, beta, or gamma sub-bands, as well as their interactions [44]. To characterize human affective states, the human prefrontal cortex (PFC) region has been widely used.…”
Section: Abci Featuresmentioning
confidence: 99%